PENYULUHAN PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) DI TKK DAN SDK SANTO BAVO KOTA MADIUN - Agus Purwanto (Universitas Merdeka Madiun, 2021)
The lack of facilities plays an important role in realizing a clean and healthy life, but it is not an obstacle for the participants and other school members of SDK Santo Bavo to be able to habituate their daily healthy lifestyle. The results of the initial survey conducted by SDK Santo Bavo students had never been given any education or counseling on the importance of clean and healthy living habits. Based on this, it is necessary to do it through counseling and training on PHBS (Healthy Day-to-Life Behavior) for students in and other residents in TKK and SDK Santo Bavo. The activity is carried out through counseling and training on how to wash hands properly with boiled water of betel leaf as a substitute for soap which has antibacterial properties. Online counseling activities through instructional videos have succeeded in increasing partners' knowledge about making green betel leaf (Piper betle L) boiled water which has antibacterial properties and steps on how to wash with boiled green betel leaf water as a substitute for soap (CTPS) which is good and correct.Â Keywordsâ€”:daily healthy behavior, green betel, antibacterial, learning videos